Testing of additively manufactured aluminium material and cross-sections in compression - Zhang, Ruizhi; Amraei, Mohsen; Piili, Heidi; Gardner, Leroy (Elsevier BV, 2026)
A comprehensive experimental investigation into the mechanical properties and structural performance of square hollow section (SHS) stub columns manufactured by laser beam powder bed fusion (PBF-LB/M) from AlSi10Mg aluminium alloy, has been conducted and is presented herein. A series of tensile and compressive coupons with different build directions, together with six SHS stub columns, were additively manufactured and tested. The PBF-LB/M AlSi10Mg material exhibited good mechanical performance and mild anisotropy, with yield and ultimate strengths of around 280 MPa and 420 MPa, respectively, and fracture strains of between about 4 % and 7 %. SHS profiles were examined to isolate the influence of the manufacturing process, enabling direct comparisons with the performance and design of conventionally produced cross-sections. The PBF-LB/M aluminium SHS stub columns failed by inelastic local buckling and exhibited similar performance to conventionally manufactured aluminium SHS in the slender range, while showing higher normalised load-carrying capacities in the stocky range. Comparisons with the existing design methods indicated that both Eurocode 9 (EC9) and the continuous strength method (CSM) can provide safe-sided resistance predictions, with the CSM yielding more accurate and consistent results.